Hepatitis C Infection and Periodontal Disease: Is there a Common Immunological Link?. (13th March 2018) - Gheorghe, Dorin Nicolae; Foia, Liliana; Toma, Vasilica; Surdu, Amelia; Herascu, Elena; Popescu, Dora Maria; Surlin, Petra; Vere, Cristin Constantin; Rogoveanu, Ion
Abstract : Hepatitis C virus (HCV) infections could have an important impact on the oral health status of patients, favoring conditions such as periodontal disease and oral cancer. The review of the existing scientific literature written in English was performed, searching for oral and periodontal manifestations of HCV infection and its impact on the oral fluids. HCV infection can determine direct extrahepatic manifestations at the oral and periodontal level including oral lichen planus, Sjögren-like sialadenitis, and oral cancer. The changes caused by the infection in the subjects' immune system, diet, and lifestyle can facilitate the development of oral conditions such as periodontal disease. Important changes also occur in the composition of the infected patients' saliva and gingival fluid. HCV-infected patients need to be carefully monitored in terms of oral health since the infection with the virus can result in oral complications. The cellular and molecular particularities of the gingival fluid of HCV-infected patients can answer some questions regarding its impact upon periodontium impairment and whether this refers to a possible bidirectional relationship, with hepatic biomarker adjustments being induced by the periodontal patients' inflammatory status.